Implementation of the Granting of Integration Rights in Overcrowded Correctional Institutions - Sutan Efendi Sitompul (PT. Sinergi Legal Publisher, 2025)
The Class II A Langkat Narcotics Correctional Institution is the UPT with the third highest overcapacity in the North Sumatra Regional Office of the Ministry of Law and Human Rights and is the detention center with the highest overcapacity among other prisons, namely 225% in 2024. Even though overcapacity is very risky, it will cause riots. This research is a juridical-empirical legal research to examine the effectiveness of the implementation of the granting of integration rights in resolving the problem of overcapacity in the Class II A Langkat Narcotics Prison. Primary data for the research were collected using the interview method, while secondary data were collected using the library method. Overcrowding at the Class II A Langkat Narcotics Prison is caused by the tendency of law enforcement officials to send criminals to prison. Integration rights are granted based on recommendations from the TPP and only cover CB, PB, and assimilation. Throughout the current period, the Class II Langkat Narcotics Prison has granted integration rights to 1,200 inmates, but remains overcrowded. This study concluded that the dominant factor causing overcapacity in the Class II A Langkat Narcotics Prison is the pattern of punishment that is still oriented towards imprisonment, the Prison plays an important role in granting integration rights except for CMK, and efforts to grant integration rights do not resolve overcapacity in the Class II A Langkat Narcotics Prison. Therefore, it is recommended that law enforcement officers educate the public so that they are not oriented towards revenge, the implementation of CMK is made easier so that the reintegration process of prisoners becomes easier, and the four subsystems in the Criminal Justice System equalize their achievements regarding the imprisonment of criminals.